2020
DOI: 10.1186/s13063-020-04973-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a probiotic on blood pressure in grade 1 hypertension (HYPRO): protocol of a randomized controlled study

Abstract: Background Arterial hypertension is a major risk factor for cardiovascular disease and leads to target organ damage including stroke, heart failure, and kidney disease. About 1.5 billion people worldwide have hypertension, and it is estimated that it causes about 8 million deaths each year. Although there are several drugs available to lower blood pressure (BP), a great proportion of treated patients does not reach recommended treatment targets. Typical antihypertensive drugs target the vessels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The latter meta-analysis also revealed a threshold of duration (> 8 weeks) and daily dose (probiotics > 10 11 colony-forming units) and a recommendation of multiple bacteria prescribed for effective intervention [33]. Additionally, innovative products such as mixed strains of live bacteria belonging to Lactobacilus and Bifidobacteria are still under trial [44]. Limited evidence of specific microbes causing hypertension prohibits the exploration of microorganism-targeting supplements via prebiotics and/or probiotics or inhibition via antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The latter meta-analysis also revealed a threshold of duration (> 8 weeks) and daily dose (probiotics > 10 11 colony-forming units) and a recommendation of multiple bacteria prescribed for effective intervention [33]. Additionally, innovative products such as mixed strains of live bacteria belonging to Lactobacilus and Bifidobacteria are still under trial [44]. Limited evidence of specific microbes causing hypertension prohibits the exploration of microorganism-targeting supplements via prebiotics and/or probiotics or inhibition via antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The latter metaanalysis also revealed a threshold of duration(>8 weeks) and daily dose(probiotics >1011 colonyforming units), and a recommendation on multiple bacteria prescribed for effective intervention (34) . As well, innovative products such as mixed strains of live bacteria belongs to Lactobacilus and Bifidobacteria are still under trial (44). Limited evidences on specific microbes causing hypertension prohibit explorations on microorganism-targeting supplement via prebiotics and/or probiotics, or inhibit via antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Where this clinical study postulates that the group treated with probiotics bifidobacterial, streptococcus and lactobacillus has converted the dietary components into active metabolites and these metabolites positively affect function of immune cells which in turn could encourage in lowering of blood pressure. 9 The meta-analysis on probiotics for antihypertensive effect from fermented milk has shown a significant effect on systolic and diastolic blood pressure (BP), 10 but during the process of investigation it is observed that the supplemented probiotics significantly affect systolic blood pleasure in patients with hypertension and diabetes, and effect on diastolic blood pressure was observed in patients with only hypertension for short period (8-10) weeks on comparing with the control group. 11 The study by Lewis et al, has supported the use of probiotics supplements for lowering systolic BP -1.58 mmHg, and diabolic BP -0.92 mmHg.…”
Section: Lowering the Blood Pressurementioning
confidence: 99%